The English aristocracy at war from the Welsh wars of Edward I to the Battle of Bannockburn - Simpkin, David (Boydell & Brewer, 2008)
A new appraisal of the military careers and activities of soldiers from elite medieval families. In 1277 the recently crowned king of England, Edward I, invaded Wales; his army, large for the time, was none the less modest by his later standards. Most of his countrymen had not been on active service outside the realm for twenty years and more, if at all, yet over the course of the following four decades, up to the battle of Bannockburn in 1314, they would be called upon to fight in four different theatres of war: in Wales, Gascony, Flanders and Scotland. Although the identities of many of the men who fought in these wars, particularly those of the thousands of peasant foot soldiers, will never be known, the names of a large proportion of the men-at-arms can be located in the records of central government. This book utilises these sources - pay-rolls, horse inventories, wardrobe books and others - to examine the military careers and activities of these men-at-arms, focusing on five main themes: mobilisation; military command; service patterns among the gentry; retinues and their composition; and 'feudal' service. Dr DAVID SIMPKIN is Research Associate at the University of Reading